2017
DOI: 10.3390/f8120482
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Soil Erosion Models for the Evaluation of Bladed Skid Trail BMPs in the Southern Appalachians

Abstract: This project measured soil erosion rates from bladed skid trails in the mountains of Virginia following a timber harvest, and compared measured erosion to four erosion model predictions produced by Universal Soil Loss Equation-Forest (USLE-Forest), Revised Universal Soil Loss Equation, v.2 (RUSLE2), Water Erosion Prediction Project-Road (WEPP-Road) using default files, and WEPP-Road using modified files in order to assess the utility of the models for these conditions. Skid trails were segregated into six bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…However, predicted erosion rates were much higher for skid trails with slopes of 6-11 degrees and spur roads at 38.56 and 56.27 Mg/ha/year, respectively. Vinson et al found a predicted erosion rate of 24.1 Mg/ha/year using USLE-Forest on bladed skid trails with water bars in Virginia on average slopes of 9 degrees, while the actual sediment trap yield was 15.2 Mg/ha/year [94]. Wade et al found erosion rates of up to 137.7 Mg/ha/year resulting from skid trails in Virginia [42].…”
Section: Erosion Ratesmentioning
confidence: 99%
“…However, predicted erosion rates were much higher for skid trails with slopes of 6-11 degrees and spur roads at 38.56 and 56.27 Mg/ha/year, respectively. Vinson et al found a predicted erosion rate of 24.1 Mg/ha/year using USLE-Forest on bladed skid trails with water bars in Virginia on average slopes of 9 degrees, while the actual sediment trap yield was 15.2 Mg/ha/year [94]. Wade et al found erosion rates of up to 137.7 Mg/ha/year resulting from skid trails in Virginia [42].…”
Section: Erosion Ratesmentioning
confidence: 99%
“…WEPP generally performs poorer than the USLE unless interior files are substantially changed and parameterized to represent site‐specific data (Vinson et al. ). Both models tend to overestimate erosion rates as they increase beyond 11.2 Mg/ha/yr (Lang et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Vinson et al. ). Climate files were created using the CLIGEN database from the nearest research station to each site.…”
Section: Methodsmentioning
confidence: 97%
“…In the Southeast, direct effects are affected by the legacy of agricultural land use (Rivenbark and Jackson 2004; Jefferson and Mcgee 2013; Lang et al 2015), geologic and hillslope factors (Rivenbark and Jackson 2004; Aust et al 2015; Vinson et al 2017a, b; Lang et al 2018), relatively high precipitation amount and intensity compared to the rest of the U.S. (Hershfield 1961; Beasley and Granillo 1988; Terrell et al 2011), and intensive management (Grace 2005). Flat areas of the Coastal Plain exhibit very little direct effects due to the combination of low slope (McBroom et al 2008; Terrell et al 2011) and rapid revegetation which helps to reduce the risk of erosion and direct effects soon after harvest (Beasley and Granillo 1988; Ensign and Mallin 2001).…”
Section: Regional Reviewmentioning
confidence: 99%